2022
DOI: 10.1111/ajd.13843
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, treatment and outcomes of 589 melanoma patients documented by 27 general practitioners on the Skin Cancer Audit Research Database

Abstract: Background and objective General practitioners manage more melanomas than dermatologists or surgeons in Australia. Previously undescribed, the management and outcomes of melanoma patients treated by multiple Australasian general practitioners are examined. Methods The characteristics, management and outcomes of 589 melanoma patients, managed by 27 Australasian general practitioners and documented on the Skin Cancer Audit Research Database (SCARD), were analysed. Results Most patients (58.9%) were males with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
2
15
1
Order By: Relevance
“…Moreover, we confirmed each primary melanoma diagnosis and obtained the type of excision by referring to the corresponding QCR pathology report, reducing the potential for misclassification that could arise by relying on MBS reimbursement data alone. Our findings are also consistent with a recent analysis of Skin Cancer Audit Research Database (SCARD) data which found that 55.9% of melanomas diagnosed in primary care were diagnosed after elliptical excision biopsy, with 74.9% undergoing wide re‐excision by the treating general practitioner 20 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, we confirmed each primary melanoma diagnosis and obtained the type of excision by referring to the corresponding QCR pathology report, reducing the potential for misclassification that could arise by relying on MBS reimbursement data alone. Our findings are also consistent with a recent analysis of Skin Cancer Audit Research Database (SCARD) data which found that 55.9% of melanomas diagnosed in primary care were diagnosed after elliptical excision biopsy, with 74.9% undergoing wide re‐excision by the treating general practitioner 20 …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with a recent analysis of Skin Cancer Audit Research Database (SCARD) data which found that 55.9% of melanomas diagnosed in primary care were diagnosed after elliptical excision biopsy, with 74.9% undergoing wide re-excision by the treating general practitioner. 20 While we found that the most frequent initial procedure was surgical excision, almost half of all melanomas were diagnosed following partial excision (shave or punch biopsy). Australian clinical practice guidelines for melanoma 8 recommend that skin lesions suspected to be melanoma be completely excised by excisional biopsy with a 2 mm margin.…”
Section: Discussionmentioning
confidence: 79%
“…71,81,[88][89][90][91] Treatment processes Thirty-two articles examined treatment processes of care. Evaluations of excision performance and adequacy of GPs (88%) usually measured the proportion of skin cancers exc ised 17,28,34,62,76,[78][79][80][81][82][83][85][86][87][88][91][92][93] or the proportion of complete (vs. partial) excisions. 23,28,34,37,71,76,82,83,86,87,[91][92][93][94] Other surgical treatment procedures, such as curettage, were also examined, 46,66,69,71,73,87 as well as non-surgical treatment such as cryotherapy.…”
Section: Preventionmentioning
confidence: 99%
“…High-risk surveillance 69,73 Using the preventive effects of ultraviolet (UV) radiation protection and vitamin B6 on AK progression 69 Information on the hazards of occupational UV radiation and behaviour change recommendations for workers with occupational exposure to UV radiation 73 Diagnostic process Unassisted visual diagnosis 17,66,[68][69][70][71]75,76 Proportion of correct diagnoses of melanoma by physician (compared to dermatologist diagnosis as gold standard) 75 29 (63) Sensitivity and specificity for melanoma detection by dermatologists and GPs during clinical skin cancer screening 68 Diagnostic-tool assisted diagnosis 17,[59][60][61][62][63][64]69,70,77,78 Proportion of melanomas that were found with the aid of totalbody photography or sequential digital dermoscopy imaging 78 Odds ratio of correctly diagnosed lesions with a dermoscope versus without a dermoscope 62 Diagnostic biopsy performance 17,23,34,46,62,69,71,75,76,[79][80][81][82][83][84]…”
Section: (7)mentioning
confidence: 99%
See 1 more Smart Citation